A qualitative exploration of the factors that influence physical activity motivation and behavior in rheumatoid arthritis - Jayarathne, Wathsala (2025)
Background: Engagement in physical activity (PA) is associated with significant physical, psychological and social benefits for individuals with Rheumatoid Arthritis (RA). Despite this, research evidence indicates that PA levels among individuals with rheumatoid arthritis (RA) remain considerably lower than those in the general population. Challenges in initiating and maintaining PA are linked to RA-specific symptoms as well as social, environmental and economic constraints. This study aimed to explore the perspectives of individuals living with RA regarding factors that influence their motivation for PA and how this motivation translates into actual PA behavior. Methods: Twelve individuals with RA (aged 30–70 years) were purposively sampled and categorized into three groups based on their self-reported levels of PA motivation and activity, using a pre-screening questionnaire. Data were collected through semi-structured interviews online and analyzed using Reflexive Thematic Analysis. Results : Five themes were identified: (1) Perceptions and reactions to RA symptoms shape motivation for PA (2) The style of motivational regulation influences PA engagement; (3) Identification of both supports and barriers affects PA motivation and behavior; (4) Peer support enables transition from motivation to PA; and (5) Autonomy in prioritizing personal abilities and preferences plays a critical role in translating motivation into PA. Conclusion: PA Motivation and behavior among individuals with RA is influenced by a complex interplay of personal, social, and contextual factors. Interventions aiming to promote PA in this population should account for individual symptom perceptions, motivational regulation styles, awareness of supports and barriers, the value of peer support, and the importance of autonomy in PA-related decision-making.